1973
DOI: 10.1002/kin.550050418
|View full text |Cite
|
Sign up to set email alerts
|

The thermal decomposition of azomethane. III. Kinetics of the noninhibited reaction

Abstract: The thermal decomposition of azomethane (A) has been studied in a static system at temperatures between 250" and 320°C and at pressures between 5 and 402 torr, with particular attention to identification of products. Major products, in decreasing order of importance, were nitrogen, methane, ethane, methylethyldiimide, dimethylhydrazone, propane, tetramethylhydrazine, ethylene, methylpropyldiimide, and methylethylhydrazone. Carbon balance at the lowest pressure and highest temperature was 92%, but decreased wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…These data are in essential agreement with our earlier studies, with quantum yields rising with increasing pressure and temperature. If reactions [7], [5], and [6] were quantitative, the quantum yield should have been unity, independent of temperature and pressure. The observed values, and their variation, probably reflect as before an incomplete and temperature-dependent quenching of Hg('P,) in reaction [7], with perhaps some loss of CH,, and thence CzH6, by the incomplete suppression of the combination reaction,…”
Section: The Mercury-photosensitized Decomposition Of Methanementioning
confidence: 99%
See 1 more Smart Citation
“…These data are in essential agreement with our earlier studies, with quantum yields rising with increasing pressure and temperature. If reactions [7], [5], and [6] were quantitative, the quantum yield should have been unity, independent of temperature and pressure. The observed values, and their variation, probably reflect as before an incomplete and temperature-dependent quenching of Hg('P,) in reaction [7], with perhaps some loss of CH,, and thence CzH6, by the incomplete suppression of the combination reaction,…”
Section: The Mercury-photosensitized Decomposition Of Methanementioning
confidence: 99%
“…2 at a methane concentration of 8 x M, much too low for the inversion reaction. Because of uncertainties in the efficiencies of reactions [5], [6], and [7], it is impossible to calculate a meaningful upper limit for reaction [2] from this system, but there is no positive evidence for its occurrence.…”
Section: The Mercury-photosensitized Decomposition Of Methanementioning
confidence: 99%
“…The decomposition was originally thought to be a true unimolecular process and the reaction pioneered experimental verification of developing theories r61. Although it is now recognized that the decomposition is a complex chain reaction [7], there is still considerable interest in the molecule as a clean supplier of methyl radicals in both photochemical [8] and thermal [9] systems. In the course of a shock tube investigation of the decomposition of azomethanel deuterated hydrocarbon mixtures by two of us (R&S), it was discovered that there were no tables of thermodynamic properties for azomethane or' azomethane.,.d 6 -in thelitemture.-As-ffi"dinarily prepared and-un~.der normal conditions, azomethane exists only in the trans form [10], and this paper deals exclusively with that configuration .. figuration.…”
Section: Estimated Uncertainties and Anharmonic Effects Inmentioning
confidence: 99%
“…I n a comprehensive study of the pyrolysis of pure azomcthane, Paquin and Forst [31] showed that ethyl radicals were formed in a complex series of reactions starting with CH3N2CH2. The presence of ethyl radicals in our reaction system could have serious implications for the interpretation of our results in that the reactions (9) (10) 2 C2H5 * n-C,Hio…”
Section: Abeckaiizsnimentioning
confidence: 99%